Osteoarthritis of the Wrist STT Joint and Radiocarpal Joint. (26th August 2012) - Wollstein, Ronit; Clavijo, Julio; Gilula, Louis A.
Abstract : Our understanding of wrist osteoarthritis (OA) lags behind that of other joints, possibly due to the complexity of wrist biomechanics and the importance of ligamentous forces in the function of the wrist. Scaphotrapeziotrapezoidal (STT) OA is common, but its role in wrist clinical pathology and biomechanics is unclear. We identified the prevalence of radiographic STT joint OA in our hand clinic population and defined the relationship between STT and radiocarpal OA in wrist radiographs. One hundred consecutive wrist clinical and radiographic exams were retrospectively reviewed. Radiographs were evaluated for the presence and stage of OA. The mean age was 61.3 (± 14.5) years. The radiographic occurrence of STT joint OA was 59% and of radiocarpal (RC) OA was 29%. Radiographic STT and RC joint OA were inversely related. Tenderness over the STT joint in physical exam was not associated with OA in the STT or other joints. STT OA in our series was not related to wrist pain. These findings support the discrepancy between radiographic and cadaver findings and clinically significant OA in this joint. The inverse relationship between STT and RC OA, as seen in scapholunate advanced collapse (SLAC) wrist, requires further biomechanical study.